Respostas
respondido por:
2
3 x² - 7 x + 2 = 0
a = 3 b = -7 c = 2
Δ = b² - 4 . a . c
Δ = (-7)² - 4 .3 . 2
Δ = 49 - 24
Δ = 25 ⇒√25 = 5
x´= - b +ou - 5/2.a
x´= - (-7) +ou- 5/2 .3
x´= 7 + 5 / 6
x´= 12/6 ⇒2
x´´ = 7 - 5/ 6
x´´= 2/6 ⇒1/3
S = { 1/3 ; 2 }
a = 3 b = -7 c = 2
Δ = b² - 4 . a . c
Δ = (-7)² - 4 .3 . 2
Δ = 49 - 24
Δ = 25 ⇒√25 = 5
x´= - b +ou - 5/2.a
x´= - (-7) +ou- 5/2 .3
x´= 7 + 5 / 6
x´= 12/6 ⇒2
x´´ = 7 - 5/ 6
x´´= 2/6 ⇒1/3
S = { 1/3 ; 2 }
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás